Analysis of volatile ingredients of selected essential oils listing relaxing action - Małgorzata Kucharska; Jadwiga A. Szymańska; Wiktor Wesołowski; Barbara Frydrych; Elżbieta Bruchajzer (Nofer Institute of Occupational Medicine, 2019)
Background Stress is a result of disturbed homeostasis and can contribute to the development of many diseases. One of the methods of combating stress is aromatherapy, which uses essential oils with a calming and relaxing effect. The aim of the work was to perform a qualitative analysis of selected essential oils with a relaxing effect. Material and Methods The research concerned 6 preparations available on the Polish market, which are attributed with anti-stress activity. The qualitative analysis was carried out by gas chromatography with mass spectrometry, which allows the determination of both main and trace substances in the tested oils. The components of individual samples were compared with data from the literature. Results In the samples tested 9-36 substances were identified. The following substances had the largest share in the composition of the studied samples: limonene (0.5−91%), linalool acetate (16.8−39.2%), citronellal (0.1−28.7%), linalool (0.8−46.5%), valerianol (17.6%), geraniol (16.4%), and citronellol (14%). Conclusions According to literature data, the main components of the studied essential oils have low acute toxicity. They can be safely used as intended and in the quantities recommended by the manufacturer. However, one should remember the potential synergistic effect (as a result of exposure to the abovementioned substances from various sources, such as: food, cosmetics, cleaning agents, etc.), as well as sensitizing effects of some compounds contained in oils. Despite the different chemical structure of active substances contained in the tested oils, it is suggested that the mechanism of the relaxing effect is identical and is associated with the inhibition of glutamatergic neurotransmission, similar to the action of benzodiazepines. Med Pr. 2019;70(2):229-47